2010
DOI: 10.1093/humrep/dep477
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of children born after frozen and fresh embryo transfer: the Finnish cohort study 1995–2006

Abstract: Embryo freezing does not adversely affect perinatal outcome in terms of prematurity, low birthweight and being small for gestational age versus the fresh embryo transfer and the outcome is similar or even better, particularly regarding fetal growth. Our study, which is one of the largest on FET pregnancies, provides further evidence on the safety of FET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
174
4
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(215 citation statements)
references
References 31 publications
25
174
4
3
Order By: Relevance
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These analyses indicate that frozen embryo state [4][5][6][7][8][9][10][11][12][13] is associated with an increased risk for LGA, and blastocyst embryo stage is associated with a decreased risk for SGA. The magnitude of the increase we found in the 2nd birthweight in the fresh/frozen pairs of siblings of +222 g is in accord with prior studies (+244 g 4 in an Australian population, +250 g 10 and +286 g 6 in Danish populations), and far exceeds the +81 g attributable only to an increase in parity.…”
Section: Discussionmentioning
confidence: 88%
“…The clinical rationale to support this technique is that the supraphysiological hormone levels resulting from ovarian hyperstimulation in the 1st trimester in fresh transfers are associated with a significantly increased risk for low birthweight (LBW, <2500 g), SGA [36], and preterm delivery [37]. In fresh donor cycles, recipients have hormone levels more comparable to those in a natural conception cycle, which may in part explain the improved rates of implantation, clinical pregnancy, and live births [38], as well as lower rates of LBW, SGA [8], and preterm birth [5]. Results of clinical studies and meta-analyses of IVF pregnancies indicate the risks for SGA, preterm birth, LBW, antepartum hemorrhage, and perinatal mortality are significantly reduced with frozen compared to those with fresh embryo transfers [2,[39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that singletons born after FET have a perinatal outcome more comparable to those born after natural conception than to those born after fresh embryo transfer (fresh ET), having higher birth weight and less pregnancy complications [2][3][4][5][6][7][8][9][10]. However, higher risk for birth of a singleton being large for gestational age (LGA) has been revealed after FET [2,3,7,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, as embryo cryopreservation became more commonplace, observational studies started to suggest that the perinatal outcomes of FETs compared to fresh transfers were Bsimilar or even better, particularly regarding fetal growth^ [3] [4]. Pregnancy and live births rates with FETs were approaching those of fresh cycles, likely through increasing use of vitrification [5].…”
mentioning
confidence: 99%